A qualitative analysis on methadone maintenance programme in the Malay language newspapers / Noor Mayudia Mohd Mothar, Hajar Abd Aziz and Shahril Anuar Abdul Ghalim - Mohd Mothar, Noor Mayudia; Abd Aziz, Hajar; Abdul Ghalim, Shahril Anuar (Universiti Teknologi MARA Cawangan Pahang, 2011)
How do the Malay language newspapers in Malaysia report the Methadone Maintenance Therapy programme? Based on this main question, the study investigates the news reports of the Berita Harian and Harian Metro, to see how the Methadone Maintenance Theraphy (MMT) were being treated in their news reports. The researchers adopted interpretive approach to analyse a sample of 11 news reports on MMT published on these newspapers throughout the year 2009. Five research questions were generated from the samples studied, namely "how do the newspaper reports on methadone-related issue", “does the report potrayed addiction as a sickness?”, “is there any misconception on the reporting of methadone issues”, “does the government care about methadone issues” and “what were people‟s reactions on MMT”. Study findings suggested that methadone has not been reported negatively by the newspapers, but there is a general idea in Berita Harian that the MMT programme has not been fully successful. On the contrary, Harian Metro prefers to give an idea that the MMT is a promising programme for drugs addicts to actually lead a normal life. These newspapers too have been treating drug addictions as sickness and not as social problem, therefore answered the main question that the newspapers has portrayed methadone as a recommended substitution for theraphy and not a type of harmful drug. News reports too were often medicallysound and had highlighted the government‟s intention to champion the programme as a main effort to help drug addicts become a productive members of the society. The study found out that the newspapers too has treated the public as the antagonist in their reports, and that it is a task uphill to correct their persistent misconception on MMT programme and drug addictions.